2012
DOI: 10.1080/13032917.2012.662907
|View full text |Cite
|
Sign up to set email alerts
|

Business performance of small tourism enterprises: a comparison among three sub-sectors of the industry

Abstract: Although numerous studies have evaluated the performance of small tourism businesses (STBs), most of them have neglected to take into account the unique characteristics of various sectors within the industry and limited the study within a specific type of location. The purpose of this study is to contribute to the knowledge pool on STBs through an analysis of differences in performance among three subsectors of the industry in an urban setting. The study attempts to understand the unique characteristics of eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 56 publications
0
18
0
1
Order By: Relevance
“…Compared to a larger company, TSMEs are in a good position to cater to consumers' increasing demand for more personalised services. This is supported by several researchers such as Akbaba (2012) and Sampaio et al (2012) where they indicated that TSMEs have greater flexibility to adapt their services and products to tourists' changing requirements and preferences compared to larger companies. Hence, standardised tourism products are no longer appealing to consumers, and tourists expect providers to tailor products and services to their specific needs and tastes.…”
Section: Literature Reviewmentioning
confidence: 78%
“…Compared to a larger company, TSMEs are in a good position to cater to consumers' increasing demand for more personalised services. This is supported by several researchers such as Akbaba (2012) and Sampaio et al (2012) where they indicated that TSMEs have greater flexibility to adapt their services and products to tourists' changing requirements and preferences compared to larger companies. Hence, standardised tourism products are no longer appealing to consumers, and tourists expect providers to tailor products and services to their specific needs and tastes.…”
Section: Literature Reviewmentioning
confidence: 78%
“…The study examines the restaurant sector, which is mainly composed of independent small and medium-sized enterprises [12].…”
Section: Resultsmentioning
confidence: 99%
“…In the tourism industry enterprises are heterogenous and offer various services, such as accommodation, restaurants, and different attractions and activities, and some enterprises provide more than one type of service. Comparative advantage may be based on either specialization on provision of a service bundle (Schneider and Bowen 1995) or on a single service, such as attraction services, or food and beverage (Akbaba 2012). As for the size of the enterprise, micro-scale and small-scale entrepreneurship is globally typical in NBT business (e.g., Hall and Boyd 2005).…”
Section: Characteristics Of the Nbt Enterprise And The Entrepreneurmentioning
confidence: 99%